Processing Characteristics of Vegetable Oil-based Nanofluid MQL for Grinding Different Workpiece Materials - Wang, Yaogang; Li, Changhe; Zhang, Yanbin; Yang, Min; Li, BenKai; Dong, Lan; Wang, Jun (International Journal of Precision Engineering and Manufacturing-Green Technology, 5(2), 2018)
Minimum quantity lubrication (MQL) is an efficient, green, and eco-friendly method of applying cutting fluids in machining processes. This study presents the processing characteristics of different vegetable oil-based nanofluid MQL for grinding various workpiece materials. The performance of three lubricant types (i.e., pure palm oil, MoS 2 nanofluid, and Al 2 O 3 nanofluid) of good lubrication performance and three types of materials (i.e., Inconel 718, ductile cast iron, and AISI 1045 steel) was evaluated in terms of force ratio, specific grinding energy, and G ratio. The optimal processing combination of lubricants and workpiece materials under the same experimental conditions was obtained using orthogonal experiment. Optimization results were verified by evaluating the morphology of the workpiece surface and grinding debris. Experimental results show the different processing characteristics of materials when various workpieces are processed using dissimilar MQL lubricants. MoS 2 nanofluid MQL is suitable for machining soft medium carbon steels, such as 45 steel, while Al 2 O 3 nanofluid is suitable for machining materials of high strength and hardness, such as nickel-based alloys.